Kontribusi Doa Mistik Karl Rahner bagi Kalangan Reformed di Era Pascakebenaran - Firdaus Salim (Asosiasi Teolog Indonesia, 2021)
Reformed conservatives tend to be suspicious and hostile to personal and subjective religious experience. Based on the works of John Calvin, Reformed theology is deemed to exclusively emphasize intellect and rationality. As the world is now facing a post-truth era, Reformed conservatives need to be aware that such era, which is generally understood in the political context, has also affected the dynamics of faith. The post-truth era has made rational and objective facts become less appealing. The subjective elements which involve mystery and awe have now deserved attention. In facing such an era, this article aims to show that the works of Calvin, especially Institutes and his commentary on the book of Psalms, are not hostile to personal religious experience. In fact, the works of Calvin are inseparable from mystical writings and even shows an openness to religious experience. Given such openness, Karl Rahner’s mystical prayers can instill the elements of mystery and awe in the faith of Reformed conservatives.